Draft Annual Plan 1976-77 Fifth Five Year Plan Union Territory of Pondicherry - Planning Commission (Planning Commission, 1976)
In the Fourth Plan this scheme was implemented to cater to the needs of Intensive Agricultural Programme whereas in the Fifth Plan for all the crops seed distribution will be covered under this scheme. The Scheme envisages distribution of improved seeds covering 1/3 of the cultivated area every year. The scheme also contemplates the following items Of work to organise seed production.
Government of Pondicherry, Planning and Research Department